Chemical disinfection as a simple and reliable method to control the amphibian chytrid fungus at breeding points of endangered amphibians - Barbora Thumsová; Emilio González-Miras; Ángel Rubio; Ignacio Granados; Kieran A. Bates; Jaime Bosch (Scientific Reports, 2024)
Abstract Chytridiomycosis caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd) is pushing amphibians towards extinction. Whilst mitigation methods were suggested a decade ago, we lack field trials testing their efficacy. We used the agrochemical fungicide, tebuconazole, to treat Bd infected breeding waterbodies of an endangered species that is highly susceptible to the fungus. Just two applications of tebuconazole led to a significant reduction in infection loads in the vast majority of sites, and at six sites the disinfection remained one/two-years post-application. Tebuconazole values drastically decreased in the waterbodies within a week after application, with no significant effects on their hydrochemical and hydrobiological characteristics. Although the use of chemicals in natural populations is undesirable, the growing existential threat to amphibians all over the world indicates that effective interventions in selected populations of endangered species are urgently needed.